OPERASI STERILISASI SEBAGAI UPAYA PENGENDALIAN POPULASI ANJING DAN KUCING DI KOTA KUPANG - Tophianong, Tarsisius Considus; Utami, Tri; Malelak, Marlin Cindy Claudya; Dami, Juni Claudia; Sanam, Maxs Urias Ebenhaizer; Sitompul, Yeremia Yobelanno; Loe, Fhady Risckhy (Universitas Nusa Cendana, 2025)
The uncontrolled population of dogs and cats in urban areas poses a significant risk for the transmission of zoonotic diseases, including rabies. As a rabies-endemic region in Indonesia, Kupang City requires effective strategies to reduce the population of rabies vector animals, one of which is through sterilization programs. This community service initiative aimed to support population control of dogs and cats as a preventive measure against the transmission of rabies. Sterilization procedures were carried out at the Veterinary Teaching Hospital of the University of Nusa Cendana during October 2024, involving 25 owned animals (both male and female dogs and cats) from various areas in Kupang, including Penfui, Oesapa, Liliba, and Naikolan. The surgeries were performed by a veterinary medical team using standard surgical techniques, with a focus on animal welfare. The activity received a positive response from the community and demonstrated that sterilization is an effective and socially acceptable method for controlling the domestic animal population. Similar programs can be implemented regularly and sustainably to support rabies elimination efforts in Kupang City.